Rationality, uncertainty, and unanimity: an epistemic critique of contractarianism. (18th March 2021) - Schaefer, Alexander
Abstract: This paper considers contractarianism as a method of justification. The analysis accepts the key tenets of contractarianism: expected utility maximization, unanimity as the criteria of acceptance, and social-scientific uncertainty of modelled agents. In addition to these three features, however, the analysis introduces a fourth feature: a criteria of rational belief formation, viz. Bayesian belief updating. Using a formal model, this paper identifies a decisive objection to contractarian justification. Insofar as contractarian projects approximate the Agreement Model, therefore, they fail to justify their conclusions. Insofar as they fail to approximate the Agreement Model, they must explain which modelling assumption they reject.